Estudio de pre-factibilidad para el montaje de una distribuidora de cementos Argos en la ciudad de Villavicencio (2017)
The pre-feasibility study for the construction of Argos´s cement distributor is a competitive project that allows the acquisition of construction materials, generating a greater confidence between constructions and clients and reduction of the transport times of the cement. It analyzes the interactions of the project with its environment, in addition to the strategic identification and alignment of the project at the global, national and regional level in order to look at its contribution. This study includes formulation studies such as market, technical, environmental, administrative and cost-benefit study, budget, investment and financing studies; Which show the profitability of the project of 21%, with an investment of 258 million pesos.